Control of a subsea PMSM with a very long feeding cable using a top-side converter – design and performance evaluation - Tang, Junfei (My University, 2016)
In oil and gas extraction applications, Permanent Magnet Synchronous Motors (PMSMs) are becoming a more preferred choice to drive Electric Submersible Pumps in order to achieve a higher efficiency than Induction Motors (IMs). In the drive system, a subsea PMSM is fed from a top-side Variable Speed Drive (VSD) through a transmission system including a step-up transformer and a long feeding cable. In this work, both the series impedance and the shunt admittance of the transmission system are taken into consideration. Sensorless control of such a subsea PMSM is implemented and evaluated in this thesis work. The sensorless control is realized by the combination of the Static Compensated Voltage Model (SCVM) method and the High Frequency Injection (HFI) method. An equivalent IM model current controller is developed to deal with the transformer shunt branch and a static estimator is implemented to estimate the PMSM voltage and current. The developed controller can successfully start and accelerate the PMSM up to 6000 rev/min within 5 s and the efficiency during steady state operation achieves 91.65% excluding the iron-core loss of the PMSM. The steady state angle estimation error with perfect parameters is -0.8506° with peak dynamic angle estimation errors at +0.7063° and -4.7335° respectively. A ±10% parameter error is acceptable for a successful PMSM start-up except for a -10% PMSM magnet flux linkage error which generates a too large angle estimation error during the start-up and leads to a start-up failure. In conclusion, the field-oriented sensorless control of a PMSM through a transmission system is possible. A five-level inverter needs to be applied to reduce the harmonic contents to realize a successful start-up of the PMSM. It is also suggested that the accuracy of the PMSM magnet flux linkage and the stator inductance are of essential importance.
Keywords: Elkraftteknik; Electric power engineering